Penentuan Karakteristik Mekanisme Gempa Tahun 2018-2019 Di Nusa Tenggara Menggunakan Metode Inversi Momen Tensor - Sri Rizki Eka Putri; Suhayat Minardi; Hiden Hiden (Kappa Journal, 2021)
Nusa Tenggara is one of the areas with a high level of seismic activity in Indonesia because this area is located between the Indian Ocean plate, which moves northward and pushes the Eurasian plate. One method that is often used to determine an earthquake's epicentre is the Tensor Moment Inversion method. This study aims to determine the moment tensor magnitude of each earthquake event and determine earthquake characteristics based on the earthquake focus mechanism in Nusa Tenggara from 2018 to 2019.  The earthquake with a magnitude of â‰¥ 5.7 SR and to find out the fault parameters, namely strike, dip, and rake using waveform data. One method that is often used to determine an earthquake's epicentre is the Tensor Moment Inversion method. The results showed that the fault planes formed were reverse faults and oblique faults. It has been calculated the moment tensor for each of the six components, namely Mxx, Myy, Mzz, Mxy, Myz and Mxz. From the results of the focal analysis of the 2018-2019 Nusa Tenggara earthquake mechanism, the values of the fault plane orientation parameters such as strike, dip and rake are obtained. For strikes in Nusa Tenggara on area 1, namely: 73° to 122°, Dip: 20° to 72° and Rake: 53° to 139°. While in field 2 for a strike, it is 232° to 280°, Dip 28° to 75°, Rake: 52° to 102°.